EFFECT OF SUPEROXIDE DISMUTASE AND CATALASE SUPPLEMENTATION IN SOYA MILK EXTENDER ON BUFFALO POST-THAW SEMEN QUALITY - NEHRU, DA; JAN, MH; KUMAR, S; SHARMA, U (The Indian Journal of Animal Reproduction, 2016)
Using the split sample technique, the semen quality parameters of 36 ejaculates from 3 buffalo bulls were studied after extension in soya milk extender ± superoxide dismutase (SOD) and catalase (CAT). Among sperm defects, tail defects increased (p
Keywords: Buffalo; Semen; Catlase; Cryopreservation; Superoxide dismutase